Humidity a potential risk factor for prosthetic joint infection in a tropical Australian hospital. Issue 12 (24th October 2018) - Armit, Drew; Vickers, Mark; Parr, Adam; Van Rosendal, Simon; Trott, Nicholas; Gunasena, Rivindi; Parkinson, Benjamin
Abstract : Background: Many pathogens of importance, including the staphylococcal species of concern in orthopaedics, demonstrate seasonal variations influenced by environmental factors. The aim of this study was to investigate the role of humidity as a risk factor for deep prosthetic joint infection following total knee arthroplasty (TKA) in a tropical Australian hospital. Methods: A retrospective cohort study of all TKAs performed over a 13‐year period was conducted at the author's institution. Univariate analysis was used to individually assess for a range of risk factors including humidity >60% and apparent temperature >30°C (86°F). Odds ratios (ORs) were reported. P ‐values <0.25 were considered as potentially important risk factors and P ‐values <0.05 were considered statistically significant. Results: A total of 1058 primary TKAs were performed with a deep prosthetic joint infection incidence of 2.7%. Four potential risk factors were identified with P ‐values <0.25: (i) humidity >60% (OR 1.4; 95% confidence interval (CI) 0.68–3.04; P = 0.221); (ii) apparent temperature >30°C (86°F) (OR 2.4; 95% CI 0.56–10.1; P = 0.174); (iii) male gender (OR 2.2; 95% CI 1.02–4.81; P = 0.057); and (iv) American Society of Anesthesiologists score of III or IV (OR 2.1; 95% CI 1.00–4.49; P = 0.064). Conclusion: Humidity and apparent temperature may be potentially important risk factors for infection following TKA.